It's Halloween, you 'fraidy mouse! - Stilton, Gern̤imo. (New York : Scholastic, 2004)
Geronimo meets a very spooky mouse, Creepella von Cacklefur, who tries to lock him up in a coffin.
"With 30 pages of Halloween games and costumes!--Cover.
410
Accelerated Reader AR
Keywords: Stilton, Geronimo (Fictitious character) -- Fiction; Halloween -- Fiction; Mice -- Fiction